Where there is road, there is fire (influence): An exploratory study on the influence of roads in the spatial patterns of Swedish wildfires of 2018 - Ferriols Pavico,Gabriel Romeo (Master Thesis in Geographical Information Science, 2023)
This study focuses on the Swedish wildfire season of 2018, when the country incurred ten times more than the average burnt area that occurred in previous years. The study aims to address a broad research question: Do roads influence the size of the burned area? This study fills the gap in research on the effects of roads in the spatial patterns of wildfires. Moreover, the research hopes to include the influence of roads in the narrative of wildfire patterns. Among other statistical methods, multivariate regression analysis was ultimately used to answer the research question. Looking at road, landcover, proximity to towns, temperature and fire weather index (FWI), it was found that the parcel sizes of forest and open landscapes influence the average burnt area of a fire. An increase of mean forest area coincides with larger fires, while the inverse is seen for open landscapes. This, in turn, suggests that roads act as fuel breaks and suppression access points by fragmenting forests. A second method that measured the ratio of a fire’s perimeter conforming to the contours of the roads supports the results of the multivariate method above. Of the fires that had edges that conformed to roads, this corresponds to 95% of the total fire area in 2018. An average of 26.7% of the ratio of road conformity was seen in these fires. The increase in conformity percentage led to smaller fire areas. The model created in this method tested what drives the amount of road conformity of fires. The amount of road density and total forest area were statistically significant in driving the conformity of fire perimeter to roads.
Keywords: Geography; GIS; Wildfire; Fire Spatial Patterns; Road; Conformity; FWI